2021
DOI: 10.36849/jdd.5014
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Chart Review of Inflamed Epidermal Inclusion Cysts

Abstract: Background: Epidermal inclusion cysts (EIC) are one of the most common forms of cysts found on and/or underneath the skin. Inflamed EICs typically show signs and symptoms such as pain and erythema, mimicking cutaneous abscess. However, prior studies have demonstrated at least 20% of lesions are culture negative. Objective: To determine the rate of culture positivity in mild inflamed epidermal inclusion cysts, in particular to identify whether empiric antibiotics are warranted. Methods: In a retrospective chart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…[ 18 ] In mildly infected epidermoid cysts (erythema or swelling without systemic symptoms), Meister H et al performed bacterial cultures on extracts from infected cysts and showed that almost half were free of pathogenic bacteria. [ 71 ] Therefore, the use of preoperative antibiotics for mildly infected epidermoid cysts needs to be chosen carefully. The anesthesia of this technique mainly uses local anesthetic with epinephrine, which is the preferred method to reduce bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] In mildly infected epidermoid cysts (erythema or swelling without systemic symptoms), Meister H et al performed bacterial cultures on extracts from infected cysts and showed that almost half were free of pathogenic bacteria. [ 71 ] Therefore, the use of preoperative antibiotics for mildly infected epidermoid cysts needs to be chosen carefully. The anesthesia of this technique mainly uses local anesthetic with epinephrine, which is the preferred method to reduce bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Inflamed EICs typically show signs and symptoms such as pain and erythema. [9] The area around the perineum is warm, humid, and has poor hygienic environment. Keloid in such condition can easily accompany cyst inflammation, leading to the additional scarring.…”
Section: Discussionmentioning
confidence: 99%